Implementasi Model Pembelajaran Teams Games Tournaments untuk Meningkatkan Hasil Belajar IPA dalam Tema Makanan Sehat di Kelas V SD Negeri Nafar - Gerson, Dina; Pelamonia, J.; La Sitiman, Hediaty (Kamboti Journal of Education Research and Development, 2022)
The problem in this research is that the learning outcomes of class V students are not optimal in thematic learning theme 3 sub theme 1 ''how the body processes food''. This happens because the learning process does not involve students optimally, learning tends to be conventional models. This research was carried out with the aim of knowing (1) improving learning outcomes by using the Teams Games Tournament (TGT) model in thematic subjects of theme 3 sub-theme 1 "how the body processes food" in class V SD Negeri Nafar. Classroom Action Research (CAR) which consists of four stages, namely: planning, action, observation and reflection. CAR research was conducted in 2 cycles consisting of two meetings. The data collection techniques in this study were tests, observations and interviews with descriptive statistical data analysis techniques and descriptive qualitative data. This study shows that student learning outcomes in learning thematic theme 3 sub-theme 1 “how the body processes food” has increased every cycle. (1) student learning outcomes before the action got an average value of 63.3 (44.4%) increased in the first cycle after the model was applied (TGT) the average value became 73.34 (55.6%) and the second cycle the value the average increased to 86.29 (83.33%). (2) student responses from the field to the application of the TGT learning model (cooperation, discipline and responsibility) in the first cycle with an average observation result of 71.6 (meeting 1) to 72.2 (meeting 2) categorized as sufficient, increasing in the cycle II with an average observation result of 85.5 (meeting 1) to 86.1 (meeting 2) with a very good score category. Thus, it can be concluded that the Teams Games Tournament (TGT) learning model can improve student learning outcomes in thematic subjects of theme 3 sub-theme 1 how the body processes food in class V SD Negeri Nafar.